Roles of Helicobacter pylori infection and cyclooxygenase-2 expression in gastric carcinogenesis - Sun, Wei-Hao (World J Gastroenterol, 2004)
AIM: Cyclooxygenase (COX)-2 is over expressed in gastrointestinal neoplasm. Helicobacter pylori (H pylori) infection is causally linked to gastric cancer. However, the expression of COX-2 in various stages of H pylori-associated gastric carcinogenesis pathway has not been elucidated. Therefore, the aim of this study was to clarify the role of H pylori induced COX-2 expression during carcinogenesis in the stomach. METHODS: Gastric biopsies from 138 subjects [30 cases of chronic superficial gastritis (CSG), 28 cases of gastric glandular atrophy (GA), 45 cases of gastric mucosal intestinal metaplasia (IM), 12 cases of moderate gastric epithelial dysplasia and 23 cases of gastric cancer] were enrolled. H pylori infection was assessed by a rapid urease test and histological examination (modified Giemsa staining). The expression of COX-1 and COX-2 in human gastric mucosa was detected by immunohistochemical staining. RESULTS: H pylori infection rate was 64.3% in GA and 69.5% in gastric cancer, which was significantly higher than that (36.7%) in CSG (P < 0.05). The positive expression rates of COX-2 were 10.0%, 35.7%, 37.8%, 41.7% and 69.5% in CSG, GA, IM, dysplasia and gastric cancer, respectively. From CSG to GA, IM, dysplasia and finally to gastric cancer, expression of COX-2 showed an ascending tendency, whereas COX-1 expression did not change significantly in the gastric mucosa. The level of COX-2 expression in IM and dysplasia was significantly higher in H pylori-positive than in H pylori-negative subjects (P < 0.01). CONCLUSION: COX-2 expression induced by H pylori infection is a relatively early event during carcinogenesis in the stomach.